Неасимптотичні оцінки ефективності випадкового кодування в системі передачі інформації двійковим симетричним каналом зв’язку з відводом - Alekseychuk, A. N.; Gryshakov, S. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The efficiency of random coding during the multiple irredundant messages transmission through a binary symmetric channel with take-off is investigated. Unasymptotic estimates of the reliability of message recovery by a legitimate recipient of information and the sustainability of their protection in take-out channel are obtained.